An integrity control model for mass data transmission under big data cloud storage. (20th August 2022) - Zhu, Zhengguo
In order to improve the control level of massive data transmission integrity, improve the space utilisation efficiency and data transmission integrity under cloud storage, an integrity control model of mass data transmission under big data cloud storage is constructed. Firstly, the basic principle of big data cloud storage is studied. The developing process of big data, data storage technology, and data retrieval technology is studied. Secondly, the mass data feature extraction model is established. The theory model and framework of feature extraction model for mass data are analysed. Thirdly, the massive data integrity control algorithm is designed based on an ant algorithm. The prior control models of single node rate are studied and system level parallel data transmission rate are analysed. Finally, simulation analysis is carried out, and the effectiveness of the proposed method is verified.